Chinese Herbal Medicine for Functional Dyspepsia With Psychological Disorders: A Systematic Review and Meta-Analysis - Luo, Xiaoying; Wang, Lin; Fang, Shuangshuang; Qing, Xiangli; Jiang, Tianyuan; Yang, Yang; Su, Xiaolan; Wei, Wei (Frontiers in Neuroscience, 2022)
Background and Aims:Functional dyspepsia (FD) is closely associated with gut-brain interaction disorder (DGBI). Chinese herbal medicine(CHM) has good concurrent effect in the treatment of FD, especially for patients with concurrent psychological disorders. A meta-analysis was designed to evaluate the efficacy and safety of CHM in the treatment of FD. Methods:The PubMed, Embase, Cochrane Library, Web of Science, Chinese Biomedical Database(CBM), Wanfang Data, China National Knowledge Infrastructure(CNKI), and China Science and Technology Journal Database(VIP) were searched to collect randomized controlled trials of FD treated with CHM.The retrieval time limit is from the establishment of the database to April 11, 2022.Two researchers independently searched databases, screende documents, extracted data, and evaluated the risk of bias of included studies. RevMan 5.4 software was used for meta-analysis.Results:A total of 11 studies including 951 patients were included. The study was divided into two parts. The first part included 5 clinical trials, including 471 patients. The control group was only treated with placebo. The results showed that the total effective rate of CHM in the treatment of FD was higher than that in the placebo group (84.5% vs 49.4%) [ P=0.01]. In addition, CHM treatment could reduce the total symptom score [P<0.0001], depression score [P = 0.03]. The second part included 6 clinical trials, including 480 patients. The control group was treated with prokinetics+deanxit .The results of second part showed that the total effective rate of CHM in the treatment of FD was higher than that of the control group (92.6% vs 78.8%) [ P＜0.0001]. In addition, CHM treatment could reduce HAMA score [P<0.00001] ,HAMD score [P < 0.00001], gastric emptying rate [p = 0.0003].The results of the two parts of the meta-analysis showed no serious adverse reactions, and there was no significant difference in the adverse reactions between the experimental group and the control group.[p=0.74];[p=0.19].Conclusion:The current evidence shows that CHM treatment has great potential and safety in alleviating the symptoms of FD and improving the psychological disorders of anxiety and depression in FD patients. Limited by the quantity and quality of included studies and other bias, the above conclusions need more high-quality studies to verify.